Transurethral unroofing of a Cowper's syringocele - Fenizia Maffucci; Jessica Clark; Anika Rastogi; Justin Friedlander; Jay Simhan (Urology Case Reports)
Syringoceles are cystic dilations of the bulbourethral gland, also known as Cowper's gland. Syringoceles are a rare pathology with no standard treatment. Herein, we report the diagnosis and endoscopic management of an imperforate syringocele causing bothersome urinary symptoms in an adult male patient. We present our technique for transurethral holmium laser unroofing of a syringocele as a feasible treatment option.